Transportation : (Cengage, 2019)
The authors provide an overview of the operating and service characteristics, cost structure, and challenges providers of transportation face. This edition highlights critical transportation management issues with insights into the strategic activities and challenges in the movement of goods through the supply chain. Completely up to date, TRANSPORTATION emphasizes global topics with the latest coverage of hard and soft technology and in-depth discussions of fuel, energy, managerial, economic, and environmental issues.